Interdependence between the family and professional work - Anna Walczak (Studia z Teorii Wychowania)
Family and work are institutions of obvious importance from the point of view of an individual and society. These institutions are connected by a network of complex interactions. On the one hand, work, the conditions in which it is performed, income derived from it, can affect the functioning of the family and the way in which it is perceived. On the other hand, the degree of involvement of individuals in the professional sphere, expectations and aspirations connected with it may be a derivative of the family situation. The article presents a comparative analysis of family and work as values based on data from the European Value Survey. This international survey, conducted since 1990 in Poland on the basis of a representative, random sample, allows searching for determinants of the attitude to family, marriage and work. It allows also to conduct a longitudinal analysis. The family is invariably the dominant value and work is the second in the hierarchy, although its meaning begins to decline. Material culture and consumerism are reflected more and more clearly in the choices made by respondents. The work ceases to be an autotelic value. Parents with three or more children assign more importance to the sphere of their professional work, although at the same time this group is the least active professionally. Gender does not differentiate the approach to "work-life-balance", although women more often emphasize the importance of egalitarian sharing of household duties.